Amino Acid and Fatty Acid Metabolism Disorders Trigger Oxidative Stress and Inflammatory Response in Excessive Dietary Valine-Induced NAFLD of Laying Hens - Jian, Huafeng; Xu, Qianqian; Wang, Xiaoming; Liu, Yating; Miao, Sasa; Li, Yan; Mou, Tianming; Dong, Xinyang; Zou, Xiaoting (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a chronic and metabolic liver disease and commonly occurs in humans with obesity and type 2 diabetes mellitus (T2DM); such a condition also exists in animals such as rodents and laying hens. Since the pathogenesis of fatty liver hemorrhagic syndrome (FLHS) of laying hens is similar to human NAFLD, hen's FLHS is commonly selected as a study model of NAFLD. Altered circulating amino acids, particularly elevated branched-chain amino acids (BCAAs) and aromatic amino acids (AAAs), are consistently reported in patients with NAFLD and T2DM. How long-term dietary individual BCAA, such as valine, impacts amino acid and fatty acid metabolism remains unknown. In this study, we demonstrated that when laying hens are fed with dietary valine at different levels (59, 0.64, 0.69, 0.74, and 0.79%) in a feeding trial that lasted for 8 weeks, long-term exposure to excessive valine diets at 0.74 and 0.79% levels could induce amino acid imbalance, impair amino acid metabolism, increase fatty acid synthesis, and inhibit fatty acid utilization. Long-term intake of excessive dietary valine could result in impaired amino acid metabolism via inhibiting C/EBP-β/asparagine synthetase (Asns). This process is mediated by downregulating the general control nonderepressible-eukaryotic initiation factor 2α- activating transcription factor (GCN2-eIF2α-ATF4) pathway and elevating corresponding circulating BCAAs and AAAs levels, which could ultimately result in amino acid imbalance. High levels of dietary valine stimulated lipid deposition by suppressing the GCN2-eIF2α-ATF4-fibroblast growth factor-19 (FGF19)-target of rapamycin complex 1 (TORC1) signaling pathway to promote fatty acid synthesis, repress fatty acid utilization, and eventually accelerate the development of NAFLD. The Spearman correlation analysis revealed that circulating amino acid imbalance is significantly associated with fatty acid metabolism disorder and enhanced oxidative stress. The inhibition of the GCN2-TORC1 pathway induced autophagy suppression to trigger liver oxidative stress and inflammatory response. In conclusion, our results revealed the adverse metabolic response to excessive dietary valine mediated by amino acid and fatty acid metabolism disorders. This study also suggested reducing dietary valine as a novel approach to preventing and treating NAFLD in humans and FLHS in laying hens.